Differing central amine receptor sensitivity in different migraine subtypes? A neuroendocrine study using buspirone - Cassidy, Eugene M; Tomkins, Esther; Sharifi, Neda; Dinan, Timothy; Hardiman, Orla; O'Keane, Veronica (Pain (Amsterdam), 2003)
Despite the importance of the 5HT1A receptor in regulating central serotonergic tone, there is a dearth of research examining its role in migraine. In this study, we examined the hypothesis that there would be altered neuroendocrine responses to a 5HT1A agonist challenge in different migraine subtypes. Prolactin (PRL) responses to the 5HT1A receptor agonist drug buspirone were compared in 30 female subjects with migraine (ten migraine with aura, MA; ten migraine without aura, MO and ten chronic/transformed migraine, CM), and ten healthy controls matched for age, gender and menstrual status. None of the subjects were taking psychotropic medication or migraine prophylactic treatment and those with formal psychiatric disorder were excluded. Endocrine responses were determined by measuring differences between baseline PRL and maximum increases post-buspirone (ΔPRL). There was no difference in baseline PRL between groups. MA subjects did not differ in their PRL responses to buspirone compared to healthy controls. The MO group had a four-fold increase in mean ΔPRL responses compared to healthy controls. Mean ΔPRL was also increased in the CM group compared to controls, but the difference was less exaggerated. This study indicates that there is supersensitive central amine receptor function in MO and CM, but not in MA. These findings support the hypothesis that central 5HT function differs among the migraine subtypes. The results also suggest that migrainous ‘transformation’ may be associated with adaptive changes in central 5HT receptor sensitivity. The relative contribution of ‘state’ and ‘trait’ receptor function to these findings as well as the possible role of dopamine receptors is discussed.